The Small-Molecule Flunarizine in Spinal Muscular Atrophy Patient Fibroblasts Impacts on the Gemin Components of the SMN Complex and TDP43, an RNA-Binding Protein Relevant to Motor Neuron Diseases - Sapaly, Delphine; Delers, Perrine; Coridon, Jennifer; Salman, Badih; Letourneur, Franck; Dumont, Florent; Lefebvre, Suzie (Frontiers in Molecular Biosciences, 2020)
The motor neurodegenerative disease spinal muscular atrophy (SMA) is caused by alterations of the survival motor neuron 1 (SMN1) gene involved in RNA metabolism. Although the disease mechanisms are not completely elucidated, SMN protein deficiency leads to abnormal small nuclear ribonucleoproteins (snRNPs) assembly responsible for widespread splicing defects. SMN protein localizes in nuclear bodies that are lost in SMA and adult onset amyotrophic lateral sclerosis (ALS) patient cells harboring TDP-43 or FUS/TLS mutations. We previously reported that flunarizine recruits SMN into nuclear bodies and improves the phenotype of an SMA mouse model. However, the precise mode of action remains elusive. Here, a marked reduction of the integral components of the SMN complex is observed in severe SMA patient fibroblast cells. We show that flunarizine increases the protein levels of a subset of components of the SMN-Gemins complex, Gemins2-4, and markedly reduces the levels of the pro-oxydant thioredoxin-interacting protein (TXNIP), an mRNA target of Gemin5. We further show that SMN deficiency causes a dissociation of the localization of the SMN complex components in the same nuclear bodies. The accumulation of TDP-43 in SMN-positive nuclear bodies is also perturbed in SMA cells. Notably, TDP-43 is found to co-localize with SMN in nuclear bodies of flunarizine-treated SMA cells. Our findings indicate that flunarizine reverses cellular changes caused by SMN deficiency in SMA cells and further support the view of a common pathway in RNA metabolism underlying infantile and adult motor neuron diseases.